THE ROLE OF ECONOMIC MANAGEMENT IN IMPROVING THE EFFICIENCY OF REAL ESTATE MANAGEMENT (Scientific electronic journal "Labor Economics and Human Capital", 2023)
The article considers one of the types of management activities in the real estate market, namely economic management of real estate. Economic management is analyzed as the process of generating income and expenses arising from the construction and operation of the entrusted facility and has a great impact on the efficiency of the facility as a whole. However, currently, there are many problems for the development of this area of real estate management, both theoretical and practical.
Keywords: real estate market, entrepreneurship, economic management, real estate management, real estate management functions.